Enhanced Antioxidant Properties of Saccharomyces-Fermented Defatted Tenebrio molitor Larvae Extract: A Sustainable Alternative Protein Source - Kyung-Yun Kang; Beom-Gyun Jeong; Jeong-Ho Kim; Kyung-Wuk Park (Fermentation)
The study aims to evaluate the feasibility of using defatted Tenebrio molitor larvae proteins as substrates in microbial fermentation, targeting the development of high-value products to combat age-related health issues. Amid increasing demand for sustainable and nutrient-dense food sources, this study investigates the potential of extracts from Tenebrio molitor larvae as functional bioactive materials. Specifically, it compares the biological antioxidant activities of defatted Tenebrio molitor larvae extracts before (SMNFE) and after (SMFE) fermentation with Saccharomyces cerevisiae. Defatting removes lipids, while fermentation enhances the extract’s bioactivity. Biochemical analyses showed that SMFE had significantly higher total polyphenol (36.04 ± 1.04 μg GAE/mg) and flavonoid (12.69 ± 0.76 μg QE/mg) contents—over three times those of SMNFE. In addition, SMFE exhibited superior radical scavenging activity, reducing power, and electron-donating ability. The total amino acid content also increased by about 18% post-fermentation, with all measured amino acids except arginine showing elevated concentrations. These enhancements demonstrate the effectiveness of yeast fermentation in improving the nutritional and functional properties of insect-derived materials. The findings support the application of fermented insect extracts in medical foods and functional cosmetics, offering a promising direction for future bioconversion technologies.